2018
DOI: 10.1073/pnas.1719627115
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of dCTP contributes to antibiotic lethality in stationary-phase mycobacteria

Abstract: Growing evidence shows that generation of reactive oxygen species (ROS) derived from antibiotic-induced metabolic perturbation contribute to antibiotic lethality. However, our knowledge of the mechanisms by which antibiotic-induced oxidative stress actually kills cells remains elusive. Here, we show that oxidation of dCTP underlies ROS-mediated antibiotic lethality via induction of DNA double-strand breaks (DSBs). Deletion of -encoded 5-OH-dCTP-specific pyrophosphohydrolase potentiates antibiotic killing of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 51 publications
4
46
0
Order By: Relevance
“…This common response involves changes in iron and redox metabolism and accumulation of ROS causing oxidative damage of DNA, RNA, and proteins, ending in cell death (7). ROS-mediated oxidative damage is also a recognized rapid killing mechanism for Mtb (8)(9)(10)(11)(12)(13). The mycobactericidals isoniazid (INH) and vitamin C have been shown to induce rapid death of Mtb by ROS generation, leading to oxidative damage (8,9,13).…”
mentioning
confidence: 99%
“…This common response involves changes in iron and redox metabolism and accumulation of ROS causing oxidative damage of DNA, RNA, and proteins, ending in cell death (7). ROS-mediated oxidative damage is also a recognized rapid killing mechanism for Mtb (8)(9)(10)(11)(12)(13). The mycobactericidals isoniazid (INH) and vitamin C have been shown to induce rapid death of Mtb by ROS generation, leading to oxidative damage (8,9,13).…”
mentioning
confidence: 99%
“…Mycobacterial MazG is involved in DNA synthesis by the hydrolysis of dNTPs and elimination of mutagenic dNTPs generated by oxidative stresses (3234). Deletion of mazG has shown to cause genomic instability in dormant Mtb (34), whereas antibiotic-induced oxidative stress reduced the survival of ΔmazG Mtb in activated macrophages (33). We found that downregulation of the expression of MSMEG_5422 , the orthologue of mazG, in M. smegmatis constitutively expressing Rv1019, made the bacteria more sensitive to H 2 O 2.…”
Section: Discussionmentioning
confidence: 99%
“…In PNAS, Fan et al (14) explore whether different classes of bactericidal antibiotics used to treat Mycobacterium tuberculosis, the causative agent of tuberculosis, share a common killing cascade. They used bactericidal antibiotics of the aminoglycoside and fluoroquinolone classes that were also used in previous bactericidal antibiotic lethality studies in E. coli.…”
mentioning
confidence: 99%
“…Fan et al (14) focus on the oxidized derivative of dCTP, 5-OH-dCTP, rather than on the oxidized derivative of guanine, 8-Oxo-G. The presence of four mutT-like genes in mycobacteria and the absence of the mutagenic signature associated with 8-Oxo-G (GC→TA) in mutational analysis studies suggest that mycobacteria are efficient in removing 8-Oxo-G from its genome.…”
mentioning
confidence: 99%
See 1 more Smart Citation